10.0k views
2 votes
Solve the following system for all solutions:

(x - 1)^2 + (y + 3)^2 = 13

x + y = -3​

1 Answer

1 vote

Answer:

  • ( -4, -1 ) and ( -9, - 6)

Explanation:

Given

  • (x - 1)^2 + (y + 3)^2 = 13
  • x + y = -3​

Solution

From the second equation we get

  • x = - y - 3

Substituting x in the first equation

  • (- y - 3 - 1)^2 + (y + 3)^2 = 13
  • (-y - 4)^2 + (y + 3)^2 = 13
  • (y+4)^2 + (y+3)^2 = 13
  • y^2 + 8y + 16 + y^2 + 6y + 9 = 13
  • 2y^2 + 14y + 12 = 0
  • y^2 +7y +6 = 0
  • (y+1)(y+6) = 0
  • y = - 1
  • y = - 6

Then

  • x = -4
  • x = - 9

Answer

  • ( -4, -1 ) and ( -9, - 6)
User Amit K Bist
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.